Diversity of nematophagous fungi associated with vegetable crops in Northern Algeria. (25th February 2022) - Sabri, Karima; Mokabli, Aissa; Mokrini, Fouad; Khayi, Slimane; Laasli, Salah-Eddine; Smaha, Djamel; Lahlali, Rachid; Hammach, Miloud; Bouchenack, Nora Serier; Hadj-Sadok, Dhaouya Nebih
Abstract: In Algeria, vegetable crops occupy an important cultivated area which accounts for 70% of the total arable land. The Sahel and coastal areas are particularly occupied by plasticulture due to favorable pedoclimatic conditions, which also allows the outbreak of various diseases and pests. Among the latter, the root-knot nematodes of the genus Meloidogyne are considered as one of the most important phytosanitary problems both in open fields and greenhouses. Biological control is a realistic alternative to replace or at least minimize the use of chemicals. The study of microflora is essential for targeting new biological agents for pest control. Two study stations belonging to Algiers are selected: Staoueli and Bordj el Kiffan. Between 2017 and 2018, soil samples were taken at random from a depth of 0 to 10 cm inside the greenhouses (treated soils) and outside the greenhouses (no treatment). The results obtained revealed a diversity of species of nematophagous fungi belonging to 8 genera, Arthrobotrys, Dactylaria, Dactylella, Myzocytium, Harposporium, Rhopalomyces, Stylopage and Triposporina . The most frequent species is Arthorobotrys musiformis with a rate of 77.5% in untreated Bordj-el-kiffan soils and 57.5% in treated soils, Staouali has a percentage of 55% and 57.5% in treated and untreated soils respectively. This study give new insights regarding the availability of endemic nematophagous fungi vegetables fields. Parasitism assessment indicated that 8 nematophagous fungi were efficient to suppress M. incognita and M. javanica by 70% and 50%, respectively. This indicate their potential as biocontrol agents against plant parasitic nematodes.